Numerical Solution Of Electrokinetics Mass Transfer Model For Protein Recovery Through Membrane Electrofilter - Syaubari syaubari; S. Nurdin (Reaktor, 2003)
Separation based on electrophoresis and electroosmosis (electrokinetics) of binary mixture of proteins (bovine serum albumin-hemoglobin) was studied on a membrane electrofilter. The mixture was separated using ionic polycarbonate membrane with variable studied consist of voltage, current, protein diffusivity, and electrophoresis mobility. Operation parameters were varied to investigate hemoglobin concentration, which pass semi permeable membrane. A model was been derived based on mass transfer principle for the case of unsteady state. For simplification, the model has been modified using Cramer Method with pseudo steady state approach to give the dimentionless form. A program for computer simulation has een written in C/C+ + language. This programming language was shown to have more effective computing ability. Furthermore, using a model and simulation on computer, the result indicates that initial mechanism of electrofilter can also be used to separate and to concentrate protein on their buffer solution.Keywords : electrophoresis, electroosmosis, protein, membrane, electrofilter